Transformative Approach in Engineering Curricula: Enhancing Computational Thinking Through Literacy Skills for Engineering Learners - R., Subashini (International Journal of Engineering Pedagogy (iJEP), 2025)
Computational thinking (CT) is a fundamental component of problem-solving and creativity in engineering education. The incorporation of reading comprehension tasks as a method to develop and enhance CT abilities in engineering students is examined in the present study. Students are motivated to analyse, assess, and synthesize knowledge by using textbased resources skills necessary for efficient CT. This method not only improves technical competency but also develops communication and critical thinking skills that are essential for handling challenging engineering problems. This study offers ideas for incorporating reading comprehension into engineering courses, drawing on cognitive theories and educational practices. The goal is to equip students with strong CT skills that are essential in today’s technology environment.